On the sensitivity of thermally and optically stimulated luminescence of α-Al2O3:C and α-Al2O3:C, Mg. (April 2017) - Kalita, J.M.; Chithambo, M.L.
Abstract: The luminescence sensitivity of α-Al2 O3 :C and α-Al2 O3 :C, Mg is of interest because of the contemporary use of these materials in dosimetry related applications. We report investigations concerning the change in sensitivity of thermoluminescence (TL) and optically stimulated luminescence (OSL) from α-Al2 O3 :C and α-Al2 O3 :C, Mg with re-use. The study was carried out on a set of un-annealed samples and others annealed at 700 and 900 °C. The TL and OSL sensitivity in α-Al2 O3 :C and α-Al2 O3 :C, Mg was found to increase with sample re-use whether the intensity was monitored as peak area or peak height for the main TL peak or, in the case of OSL, as the maximum intensity or the area under a decay curve. The fractional increase in area under either the main TL peak or the OSL decay curve exceeds that of the TL peak height or maximum OSL intensity when samples are re-used. However, when un-annealed samples are used, any increase in TL peak height or peak area per measurement is less than observed in annealed samples. It is also interesting to note that the change in maximum OSL intensity or OSL area is minimal for samples annealed at 900 °C. In general, the TL sensitivity in α-Al2 O3 :C increases more than that in α-Al2 O3 :C, Mg with re-use. On the other hand, the OSL sensitivity in α-Al2 O3 :C, Mg increases more than that in α-Al2 O3 :C with re-use. These findings suggest that it is advisable to take into account the fractional increase in sensitivity per measurement when one uses α-Al2 O3 :C as a TL dosimeter and α-Al2 O3 :C, Mg as an OSL dosimeter. Highlights: TL sensitivity of α-Al2O3:C and α-Al2O3:C, Mg changes with re-use. OSL sensitivity of α-Al2O3:C and α-Al2O3:C, Mg changes with re-use. TL/OSL sensitivity of α-Al2O3:C and α-Al2O3:C, Mg depends on annealing temperature.